Introducing reduced graphene oxide to enhance the thermal properties of cement composites. (May 2020) - Jing, Guojian; Ye, Zhengmao; Wu, Jiaming; Wang, Shuxian; Cheng, Xin; Strokova, Valeria; Nelyubova, Viktoria
Abstract: For modern concrete technology, how to control the generation and propagation of thermal cracks is still a challenge. The large temperature gradient between the internal and external surface is primarily responsible for the cracks. The present study successfully develops a new avenue to minimize the temperature difference of cement composites by introducing reduced graphene oxide (rGO). The effective dispersion of rGO in cement matrix is achieved by applying the polycarboxylate dispersant. The incorporation of rGO enhances the thermal properties of mortar, resulting in a lower temperature difference. The uniformity of calculated heat flux and early-age shrinkage of cement composites are improved by adding rGO. Moreover, the mechanical strength slightly increases at 3 days up to doping 0.6 wt % rGO and does not display significant enhancement after 28 days. Obtained results demonstrate doping rGO is a promising approach to reduce the thermal stress and restrain the development of thermal cracks.